Exploring marine conservation and climate adaptation synergies and strategies in European seas as an emerging nexus: a review - Gregory Fuchs; Fenja Kroos; Cordula Scherer; Miriam Seifert; Nico Stelljes (Frontiers in Marine Science)
Europe’s marine and coastal ecosystems provide essential ecosystem services, however, their ability to support climate adaptation and mitigation is increasingly threatened by anthropogenic pressures. This systematic literature review identifies and evaluates integrated approaches that align marine conservation with climate adaptation, revealing untapped potential in leveraging synergies across governance, planning, management, and sectoral integration. Despite extensive research in both fields, their interlinkages remain underexplored, with implementation often fragmented and in early development stages. Our findings identify major nexus approaches, particularly ecosystem-based strategies, which, when effectively applied, strengthen the resilience of coastal social-ecological systems. Central nexus measures include climate-smart marine protected areas, ecosystem restoration (e.g., for wetlands, reefs, dunes, seagrasses), pollution control, and hybrid coastal protection solutions. However, their success hinges on cross-sectoral coordination, robust governance, adaptive management, effective stakeholder engagement, long-term monitoring, and financial sustainability. A critical gap in integrating marine conservation and climate adaptation reflects not only a research shortfall but also barriers in policy and practice. Addressing trade-offs between conservation and adaptation is crucial to maximizing synergies while avoiding unintended socio-economic consequences. The study underscores the need for science-policy integration and transformative governance frameworks to implement nexus strategies at scale. Strengthening regulatory coherence, integrating adaptation into marine spatial planning, and expanding financing mechanisms are critical to operationalizing these measures effectively. These insights provide pathways for policymakers, researchers and practitioners to develop resilient, adaptive marine and coastal management approaches in the face of accelerating climate change.